(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background. Excess body weight is one of the most important modifiable risk factors for the development of arterial hypertension and cardiovascular complications. Increasing body mass index (BMI) is associated with adverse myocardial remodeling, disruption of the circadian blood pressure (BP) pattern, and progressive target organ damage. However, the relationship between excess body weight, left ventricular (LV) geometry, and the 24-hour BP profile in men has not been sufficiently investigated. Objective. To evaluate the association between excess body weight, left ventricular remodeling, and abnormalities of the circadian blood pressure profile in middle-aged men with arterial hypertension. Materials and Methods. This cross-sectional study included 73 male aged 20-45 years with grade I-II arterial hypertension. All participants underwent anthropometric assessment, transthoracic echocardiography with evaluation of LV structural and geometric parameters, and 24-hour ambulatory blood pressure monitoring (ABPM). According to BMI, participants were classified into three groups: normal weight, overweight, and class I obesity. Results. The prevalence of concentric LV remodeling and abnormal circadian BP patterns increased progressively with increasing BMI. Patients with class I obesity demonstrated a significantly higher prevalence of the non-dipper BP profile and a lower prevalence of the physiological dipper pattern. Echocardiographic evaluation also revealed a stepwise increase in interventricular septal thickness, left ventricular posterior wall thickness, left ventricular mass, and left ventricular mass index with increasing body weight. Conclusion. Excess body weight in men with arterial hypertension is associated with more pronounced left ventricular remodeling and disturbances of the circadian blood pressure profile. These findings emphasize the importance of a comprehensive therapeutic strategy that includes not only achieving target blood pressure levels but also effective weight management to slow the progression of target organ damage and reduce long-term cardiovascular risk.